Temperature variations and soil thermal properties at the Nigeria mesoscale experiment site, Ibadan, Nigeria (2019)
Soil temperature has been observed to depend on a number of factors, which also determine the surface temperature. In this study, soil temperature at the Nigeria Mesoscale Experiment (NIMEX) site, Ibadan (7.4398° N, 3.8930° E) was investigated and the soil thermal properties were estimated for the period of March, 2006 to January, 2007 using Kersten model. The rainy seasons had increased the soil moisture content and soil thermal properties while the dry seasons had low soil moisture content and soil thermal properties. The maximum temperature of 32.10° C at the 30cm depth was measured in November 2006 during the dry season and the minimum temperature 26.80° C was measured at 5cm depth in September 2016 during the wet/rainy season. Soil moisture, thermal conductivity, thermal diffusivity and volumetric heat capacity had their maximum value of 20.52m3m-3, 1.006 Wm-1K-1, 1.07*10-8m2s-1 and 0.91*108Jm- 3K-1 in September 2006 respectively. The minimum values for soil moisture, thermal conductivity and volumetric heat capacity occurred in January, 2007 with values of 15.75 m3m-3, 0.90 Wm-1K-1 and 0.91*108Jm-3K-1 respectively, and the minimum value of 0.85*10-8m2s-1 for thermal diffusivity occurred in July 2006.